(untitled) (Research, Society and Development, 2022)
Ayapana triplinervis (Vahl) R.M. King & H. Robinson is a plant species native to the Amazon region, belonging to the Asteraceae family, popularly known as Japana, which can be found throughout Brazil and in other Latin American, Caribbean and Asian countries. In folk medicine, there are several claims of medicinal use, this therapeutic potential of A. triplinervis has aroused the interest of many research groups around the world, which seek to elucidate its chemical constitution and evaluate its activities against biological systems, in vitro and in alive. Therefore, the objective of this work is to carry out a survey of all the studies already published of A. triplinervis in relation to its traditional use, chemical constituents and biological activity, in order to contribute to the scientific community that is interested in deepening its knowledge about this species. medicinal plant. A bibliographic survey was carried out, where searches were made in databases from the medicinal plant Ayapana triplinervis (Vahl) R.M. King & H. Robinson and their scientific synonyms published on the website http://www.worldfloraonline.org, the databases used in the research were SCOPUS, WEB OF SCIENCE, SCIELO and PUBMED. From this review we can observe chemical compounds identified in the species, as well as potential biological activities related to the use of Japana, being evidenced in the published works the activities: antimicrobial, antiviral, antinociceptive and anti-inflammatory with promising results for the research and development of new drugs.